Integrated real-time production scheduling of a multiple cryogenic air separation unit and compressor plant. (2nd September 2017) - Adamson, Richard; Hobbs, Martin; Silcock, Andy; Willis, Mark J.
Highlights: Application of production scheduling with real-time optimisation. Integration of site-wide and real-time optimisation with existing MPC strategies. Management of ASU transitions and compression network change within RTO. Optimisation implemented using mixed integer linear programming. Abstract: The development and application of an integrated real-time production scheduling and control strategy for a multiple cryogenic air separation unit (ASU) and compressor plant is discussed. Using a top-down optimisation approach, the operational targets for ASU production and compressor configuration are obtained for a given customer demand and subsequently managed using a real-time optimisation strategy. This is integrated with existing control to implement the steady-state configuration targets subject to process disturbances, power price fluctuations and against network change penalty weightings. Network material balance and network component operating constraints are met while simultaneously minimising plant reconfiguration costs during transient operation which occurs as a result of changing demands. Implemented using mixed integer linear programming, it is demonstrated that the two-stage optimisation strategy improves site operating costs by an average of 5% over the considered trial period (which would translate into substantial cost savings for such an energy intensive process).